Embryonic alternatives amid London's housing crisis. Issue 5 (3rd October 2017) - Wilde, Matt
Abstract : One of the hallmarks of the austerity agenda in the UK has been the discursive prevalence of both scarcity and individual responsibility as justifications for drastic cuts to public services. In the context of London's housing crisis, cuts to welfare for low‐income tenants have resulted in an alarming rise in evictions and homelessness within a wider context of displacement and gentrification in the city. This article explores how embryonic resistance to these processes, as well as to deeper histories of dispossession, is undertaken by housing activists through a set of ethical practices that promote collectivized care and mutual support among those faced with housing precarity. Although these emergent networks are fragile, it argues that a nascent housing movement in London offers some compelling glimpses of a more hopeful politics that may lie just beneath the surface of the present moment.